Application of the Principle of Consensuality and its Legal Implications In Electronic Contracts at Shopee - SUTIYOSO, Bambang; PARMITASARI, Indah (PT Keberlanjutan Strategis Indonesia, 2023)
Abstract This study aims to examine and analyze the application of the principle of consensuality in electronic contracts at Shopee: and how the legal implications of the application of the principle of consensuality in electronic contracts at Shopee. The research method used is normative juridical with a statutory and conceptual approach, using secondary legal data and analyzed with a qualitative descriptive method. The results showed that in electronic contracts at Shopee, the principle of consensualism has been applied. In this case, the electronic contract is carried out by means of a click-wrap agreement, namely to determine the agreement in the e-contract is when the party receiving the offer